2020
DOI: 10.1242/jcs.246983
|View full text |Cite
|
Sign up to set email alerts
|

Pex24 and Pex32 are required to tether peroxisomes to the ER for organelle biogenesis, positioning and segregation in yeast

Abstract: The yeast Hansenula polymorpha contains four members of the Pex23 family of peroxins, which characteristically contain a DysF domain. Here we show that all four H. polymorpha Pex23 family proteins localize to the endoplasmic reticulum (ER). Pex24 and Pex32, but not Pex23 and Pex29, predominantly accumulate at peroxisome–ER contacts. Upon deletion of PEX24 or PEX32 – and to a much lesser extent, of PEX23 or PEX29 – peroxisome–ER contacts are lost, concomitant with defects in peroxisomal matrix protein import, m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(74 citation statements)
references
References 58 publications
(90 reference statements)
7
67
0
Order By: Relevance
“…3 D). In line with our earlier observations, peroxisome-ER contacts require Pex32 (Wu et al, 2020). The distance between peroxisomes and ER increased in the absence of Pex32, whereas associations with the PM were unaffected in these cells (Fig.…”
Section: Inp1 Colocalizes With Pex3 At Peroxisome-pm Contactssupporting
confidence: 93%
See 1 more Smart Citation
“…3 D). In line with our earlier observations, peroxisome-ER contacts require Pex32 (Wu et al, 2020). The distance between peroxisomes and ER increased in the absence of Pex32, whereas associations with the PM were unaffected in these cells (Fig.…”
Section: Inp1 Colocalizes With Pex3 At Peroxisome-pm Contactssupporting
confidence: 93%
“…Pyc1 was used as a loading control. contact sites (Wu et al, 2020). To analyze the contribution of ER and PM contact sites, we compared peroxisome inheritance in inp1, pex32, and inp1 pex32 strains.…”
Section: Inp1 Colocalizes With Pex3 At Peroxisome-pm Contactsmentioning
confidence: 99%
“…interplay and membrane contacts have also been reported (van Roermund et al, 2000;Dulermo et al, 2015;Mattiazzi Ušaj et al, 2015;Mindthoff et al, 2016;Kustatscher et al, 2019;Wu et al, 2020).…”
Section: Discussionmentioning
confidence: 82%
“…Although initially reported at the peroxisome (Brown et al, 2000, Tam & Rachubinski, 2002, Vizeacoumar et al, 2003, Vizeacoumar et al, 2004), later studies either reported dual localization to peroxisomes and ER (David et al, 2013, Yan et al, 2008) or exclusive localization at ER subdomains (Joshi et al, 2016, Mast et al, 2016, Wu et al, 2020). A recent study characterizing O. polymorpha Pex23 family members reported the involvement of PEX24 and PEX32 in peroxisome- ER contact sites (Wu et al, 2020). This could explain the previous contradictory reports on their localization, as they can be expected to be present in spots where peroxisomes and ER interact.…”
Section: Resultsmentioning
confidence: 99%
“…O. polymorpha PEX11 has been implicated in peroxisome segregation during cell division (Krikken et al, 2009). S. cerevisiae PEX11 and PEX34 are involved in peroxisome-mitochondria contact sites (Shai et al, 2018, Ušaj et al, 2015), while O. polymorpha PEX11 has been implicated in peroxisome-ER contact sites (Wu et al, 2020). S. cerevisiae PEX11 has also been proposed to act as a pore-forming protein (Mindthoff et al, 2016) and has been implicated in medium chain fatty acid oxidation as well (van Roermund et al, 2000).…”
Section: Resultsmentioning
confidence: 99%